Reconstitution of dominant kombucha strains to enhance functional properties and product quality - Liao, Ting; Li, Li; Yang, Jing-Rong; Shao, Shi-Ting; Zheng, Wei-Ming; Cheng, Lai-Hoong; Fan, Li (Frontiers in Nutrition, 2025)
IntroductionPrevious studies have shown that yeasts, acetic acid bacteria, and lactic acid bacteria (LAB) dominate the fermentation of kombucha. However, the functional contributions of defined microbial combinations remain insufficiently characterized. This study aimed to isolate dominant kombucha microorganisms and construct synthetic consortia to evaluate their effects on fermentation performance and product quality.MethodsSix dominant strains—Saccharomyces cerevisiae (JQ-1), Pichia manshurica (JQ-2), Acetobacter papayae (CQF1), Acetobacter tropicalis (CQF2), Lactobacillus plantarum (RXA1), and Lactobacillus fermentum (RXA2)—were isolated and reconstituted into three synthetic consortia. Fermentation products were analyzed for phenolic content, antioxidant capacity, organic acids, free amino acids, caffeine, sensory attributes, and microbial safety.ResultsAll synthetic consortia significantly increased phenolic content, antioxidant activity, and organic acid accumulation, while reducing free amino acids and caffeine levels. Among them, Consortium B (JQ-1 + JQ-2 + CQF1 + CQF2) achieved the highest sensory acceptability due to its balanced acidity and flavor profile. Microbial safety assessments confirmed the absence of pathogenic microorganisms.DiscussionThese results demonstrate that rationally designed microbial consortia can effectively improve the functional quality, sensory properties, and safety of kombucha. The study provides a scientific basis for developing standardized and optimized industrial fermentation strategies.